PERAN PENGURUS REMAJA MASJID NURUL TARBIYAH ABDUL AZIZ DALAM MEMBENTUK KARAKTER REMAJA DI KELURAHAN PASARWAJO - Azman Fauzan; Muhammad Ridwan; Maudin (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
This study aims to analyze adolescent character, the role of the Youth Mosque Management of Nurul Tarbiyah Abdul Aziz, and the supporting and inhibiting factors in shaping adolescent character in Pasarwajo Village. This research uses a qualitative approach with a field research design. Data were collected through observation, interviews, and documentation involving mosque youth administrators, community leaders, and local residents as informants. The results show that adolescent character in Pasarwajo Village is diverse; some adolescents demonstrate positive traits such as politeness, social awareness, and active participation in religious activities, while others show low discipline and limited involvement in positive activities. The Youth Mosque Management plays a significant role in shaping adolescent character through religious activities, guidance, social engagement, and by acting as role models and social controllers. Supporting factors include community support, family involvement, and mosque facilities, while inhibiting factors include low interest among adolescents, negative peer influence, and uncontrolled use of technology. Therefore, collaboration between mosque youth organizations, families, and the community is essential to develop better adolescent character.